The Spatial Context of the Removal of Sustainable Rice Fields in Surakarta City - Rosyada, Nisrina Dhiya; Sudaryono (Indonesian Journal Publisher, 2025)
The area designated for agriculture is diminishing due to urban expansion. Control measures play a crucial role in preventing the conversion of agricultural land. The limited availability of land in Surakarta City serves as justification for the city government, as a regulatory body, not to designate agricultural areas in the Surakarta City spatial planning (RTRW) for the years 2021-2041. When the central government enacted a policy regarding the protection of rice fields, the Surakarta City administration requested its exclusion from the decree. This study adopts a case study approach to provide an overview of agricultural lands in Surakarta City that have been omitted from this policy. Data were gathered through interviews, observations, and document analysis. It has been observed that Surakarta City still possesses rice fields that local farmers cultivate, and these farmers are residents holding Surakarta ID cards. This situation leads to a realization that the city’s planning fails to support sustainable development despite agriculture not being the predominant occupation in the area. In addition to the ineffective control efforts at the city level, this phenomenon highlights the need for agricultural empowerment to ensure the continued development of socio-cultural practices.